Simultaneous transfemoral transcatheter mitral and tricuspid valve edge-to-edge repair (using MitraClip system) completed by atrial septal defect occlusion in a surgically inoperable patient. First-in-human report - Kowalski, Marek; Franz, Norbert; Ritter, Frank; Hofmann, Steffen; Stabel-Mahassine, Chourok; Warnecke, Henning; Thale, Joachim (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2015)
Transcatheter transfemoral mitral valve repair using the MitraClip system (Abbott Vascular, USA) is used in high-risk or inoperable patients with severe mitral regurgitation. We report the first-in-human simultaneous transfemoral clipping of the mitral and tricuspid valve completed by occlusion of an atrial septal defect (ASD). The procedure was performed in an 84-year-old patient in October 2015. After effective reduction of mitral and tricuspid regurgitations using the MitraClip system a PFO Occluder (St. Jude Medical, USA) was implanted. Transfemoral simultaneous mitral and tricuspid valve repair using the MitraClip system with ASD occlusion seems to be an effective therapy for high-risk or inoperable patients.